ANALYSIS OF LEARNING DIFFICULTIES AND STUDENT MORAL RESPONSIBILITIES - Kogoya, Willius; Uruwaya, Hiskia Uruwaya; Dapla, Mais; Yikwa, Siwan (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The learning process does not always run smoothly. Under certain conditions, various obstacles may be encountered so that students often do not attend classes, do not complete class assignments, and are late for re-registration. This research examines learning difficulties and students' moral responsibilities. The study used a qualitative method with a case study approach to 55 students of Civics Study Program. The research period lasts for six months, namely throughout the even semester of the 2021-2022 academic year. From the research results, the following conclusions are obtained: 1) student learning difficulties are caused by factors of low student basic skills, interest, motivation, economic conditions, environment, facilities and infrastructure. 2) Students have not shown moral responsibility to complete academic assignments. If this is not addressed immediately, then not only will learning not achieve the expected results, but furthermore, responsible Indonesian citizens will not be created.